Analisis Pelaksanaan Pembelajaran Pendidikan Agama Islam Berbasis Higher Order Thingking Skills (HOTS) di SMA Negeri 1 Gandapura - Putri, Rizka Nadia; Wardhani, Nia; Dayusman, Edo Alvizar (Pascasarjana IAIN Lhokseumawe, 2024)
This study aims to analyze the implementation of Higher Order Thinking Skills (HOTS) in Islamic Religious Education (PAI) learning at SMA Negeri 1 Gandapura and to identify the challenges encountered in its application. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that PAI teachers have made efforts to integrate HOTS elements in lesson planning through 4C-based lesson plans (Critical thinking, Creativity, Collaboration, and Communication) and by applying discussion methods and contextual learning that connect Islamic values with students’ real-life situations. However, the classroom implementation of HOTS still faces several obstacles, including limited teacher understanding of HOTS concepts, low student engagement in critical thinking processes, and inadequate facilities and evaluation systems to support analytical and creative learning. These findings indicate that the implementation of HOTS in PAI is in a transitional phase from conceptual planning to reflective practice. The study recommends strengthening teachers’ pedagogical competencies through reflective training, optimizing technology-based learning media, and developing evaluation systems that foster analytical thinking and moral application in daily life.